Effect of Adding Temulawak (Curcuma xanthorrhiza) Extract to Artificial Feed on the Growth of Nile Tilapia (Oreochromis niloticus) Fingerlings: PENGARUH PENAMBAHAN PERASAN TEMULAWAK (Curcuma xanthorrhiza) PADA PAKAN BUATAN TERHADAP PERTUMBUHAN BENIH IKAN NILA (Oreochromis niloticus) - Haikal, Rifan Fikri; Budiyanto, Didik; Agustini, Maria (Jurnal Perikanan Pantura (JPP), 2026)
The growth of Nile tilapia (Oreochromis niloticus) in aquaculture is strongly influenced by feed quality and feed utilization efficiency. The addition of natural herbal ingredients such as Java turmeric (Curcuma xanthorrhiza) to fish feed is known to contain bioactive compounds that may enhance appetite, improve digestion, and support fish growth. This study aimed to determine the effect of adding Java turmeric extract to feed on the growth of Nile tilapia juveniles and to identify the most effective dosage. The study employed a Completely Randomized Design (CRD) with four treatments of Java turmeric extract added to the feed: 300 ml/kg feed, 400 ml/kg feed, 500 ml/kg feed, and 600 ml/kg feed, each with six replications. Nile tilapia juveniles were reared for 30 days with a stocking density of 10 fish per culture container. The observed parameters included absolute weight gain and water quality parameters consisting of temperature, pH, and dissolved oxygen. The data were analyzed using analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test at a 95% confidence level. The results showed that the addition of Java turmeric extract to the feed had a significant effect on the growth of Nile tilapia juveniles. The treatment with a dosage of 500 ml/kg feed produced the highest absolute weight gain of approximately 5.9 g, followed by 600 ml/kg feed (±4.9 g) and 400 ml/kg feed (±4.6 g), while the lowest growth was observed in the 300 ml/kg feed treatment (±4.0 g). Water quality during the rearing period remained within the optimal range for tilapia culture, with temperatures of 26.4-28.2 °C, pH of 7.8-8.1, and dissolved oxygen of 4.49-6.41 mg/L. The dosage of 500 ml/kg feed was the most effective treatment for improving the growth of Nile tilapia juveniles.